ANALISIS KERUSAKAN PERKERASAN JALAN DENGAN METODE PCI DAN BINA MARGA (STUDY KASUS : JALAN SIMPANG EMPAT – PANTI (STA 7+000 – STA 9+000) NAGARI TALU KABUPATEN PASAMAN BARAT) - Wanora, Wellyna; Dewi, Selpa; Zulhedi, Zulhedi (Ensiklopedia Research and Community Service Review, 2024)
Roads play a very important role in people's lives in supporting the pace of the economy and regional development. If there is damage to the road it can cause an accident. The aim of this research is to determine the types of damage and index values for the Nagari Talu road, West Pasaman Regency, so that it can compare the road condition values based on two methods, namely, the PCI (Pavement Condition Index) method and the Bina Marga method. The assessment of road conditions using the PCI method is ranked from 0-100, while the Bina Marga method is based on the order of road priority with a value range of 0-7. The types of damage found on the 2 km long Nagari Talu road included holes, crocodile skin cracks, longitudinal cracks, transverse cracks, patches, loose grains and wavy ones. In the PCI method, the average value of 57.14 is good road conditions. In the Bina Marga method, the priority order value is 5.35, so the road is under periodic maintenance.Keywords: Road damage analysis, PCI method, Bina Marga method, Jalan Nagari Talu West Pasaman Regency.